UPAYA LANSIA DALAM MENJAGA KESEIMBANGAN TUBUH DI PANTI SOSIAL LANJUT USIA HARAPAN KITA PALEMBANG - Fera Siska (LPPM STIKes Mitra Adiguna, 2023)
Elderly is a group of people aged 60 years and over. This type of research uses a qualitative method with a phenomenological study approach, namely to explore the efforts of the elderly in maintaining body balance at the Harapan Kita Social Institution for the Elderly in Palembang. Research results The results of interviews and observations on Mrs